Appropriate bowel preparation for laparotomy gynecologic surgery: A prospective, surgeon-blinded randomized study - Wasakorn Suadee (2018)
© 2016 S. Karger AG, Basel. Objective: To compare the surgeon's satisfaction during gynecological laparotomy surgery and patient's satisfaction as well as quality of life (QOL) among 3 groups of bowel preparations: no enema vs. sodium chloride enema vs. soap-suds enema (SSE). Materials and Method: Three hundred and thirty three women undergoing gynecological laparotomy surgery and without risks to bowel lumen entry between November 2014 and October 2015 were randomized to receive no enema (n = 111), sodium chloride enema (n = 111) or SSE (n = 111) for bowel preparation. Surgeons, who were blinded for the type of bowel preparation, assessed the surgical visualization and the efficacy of bowel packing. The patients' satisfaction and the QOL were also assessed on the days of admission, operation, post-operation, and discharge. Results: The patients' features of the 3 groups were well balanced. The surgeon's satisfaction was rated excellent as 56.8, 63.1 and 65.8% in the no-enema, sodium chloride and SSE groups (p = 0.830), respectively. The patients in the no-bowel-preparation group were satisfied more significantly than the other groups (p = 0.001). No significant differences in QOL were observed among the 3 groups. Conclusion: The type of bowel preparation for exploratory gynecologic surgery did not affect the surgical visualization and the QOL of the patients.